Victor Le Vine's shorter Cameroon writings, 1961-2007 - Krieger, Milton (Langaa Research & Publishing CIG, 2015)
From his first research there in 1959 until shortly before his death in 2010, Victor Le Vine was a major Cameroon scholar. What he wrote during Cameroon's first half-century of independence carries implications for the years ahead. This volume introduces and presents eight of his short writings, 1961-2007, five never previously published. They demonstrate his mastery of the intricacies and the sweep of the country's governance history, and both his own and Cameroon's importance for African Studies at large.